EFFECT OF ANTI-HALITOSIS-MOUTH RINSES ON SURFACE PROPERTIES OF RESIN BASED RESTORATIVE DENTAL MATERIALS - Meriç Berkman; Ezgi Altuntaş; Safa Tuncer; Mustafa Demirci; Ferda Karabay; Neslihan Tekçe (Cumhuriyet University, 2022)
Objectives: This in-vitro study aimed to investigate the effect of five different types of mouth rinses used for halitosis on color stability and surface roughness of two types of restorative materials. Materials and Methods: In this study, a total of 120 disc-shaped samples (10x2mm) were prepared with nano-hybrid resin composite (Filtek Z550) and giomer (Beautifill II) materials. Randomly selected samples were divided into six groups as five different mouth rinses (Listerine Fresh Burst, Listerine Total Care, Colgate Plax, Oderol, Halitosil) and a control group (distilled water). Initial color values were measured by spectrophotometer (Easyshade Compact) according to the CIELAB system, and roughness values (Ra) were measured by contact profilometer (Surtronic 25). All specimens were incubated in mouth rinses at 37° C for 12 hours and measurements were performed in the same procedure. Data were analyzed by using Kruskal-Wallis H and Bonferroni Post Hoc tests with the SPSS 24.0 program at a significance level of 0.05. Results: The results of this study showed that there was not a statistically significant increase in surface roughness values. There was a significant change in CIELAB values in all of the Beautifil II materials after the immersion in mouth rinses (P<0.05). There was a statistically significant difference between the color change values of Beautifil II and Filtek Z550 materials kept in the same mouth rinses (P<0.05). Beautifil II was exhibited color change with values above the clinically acceptable limit (ΔE>3.3). Conclusions: Color changes occurred in both of the restorative materials kept in different mouth rinses.